The effect of menthol mouth rinsing and fluid temperature on male cycling performance in thermoneutral conditions - Gavel, E. H.; Hawke, K. V.; Logan-Sprenger, H. M. (Nutrients, 2024)
Purpose: The purpose of this study was to determine the effect of a menthol (MEN) mouth rinse (MR) on cycling time trial (TT) performance in thermoneutral conditions and to explore the impact of fluid temperature (cold water [CW] or thermoneutral water [TNW]) on MEN`s effect on performance.